Slope-based and geometric encoding of a goal location by the terrestrial toad, Rhinella arenarum - Sotelo, María Inés (2017)
The current study was designed to test for the ability of terrestrial toads, Rhinella arenarum, to use slope as source of spatial information to locate a goal, and investigate the relative importance of slope and geometric information for goal localization. Toads were trained to locate a single, water-reward goal location in a corner of rectangular arena placed on an incline. Once the toads learned the task, three types of probe trials were carried out to determine the relative use of slope and geometric information for goal localization. The probe trials revealed that the toads were able to independently use slope, and as previously reported, geometry to locate the goal. However, the boundary geometry of the experimental arena was found to be preferentially used by the toads when geometric and slope information were set in conflict.